Social and Community Benefits and Limitations of Urban Agriculture: FCS3378/FY1517, 1/2023 - Papanek, Alicia; Campbell, Catherine G.; Wooten, Hannah (EDIS, 2023)
This publication provides an overview of the benefits of urban food production, along with potential challenges that can limit the success of these operations. Written by Alicia Papanek, Catherine G. Campbell, and Hannah Wooten, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2023.